2022
DOI: 10.3390/ijerph19073873
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Falls: A Qualitative Study of the Experiences of People Receiving Haemodialysis

Abstract: The prevalence of falls is high in people receiving haemodialysis (HD). This study aimed to explore the experiences of people receiving HD who had fallen in the last six months. A qualitative study, informed by constructivist grounded theory, used semi-structured interviews in combination with falls diaries. Twenty-five adults (mean age of 69 ± 10 years, 13 female, 13 White British) receiving HD with a history of at least one fall in the last six months (median 3, IQR 2–4) participated. Data were organised wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Recent studies have concluded that focus on the identification of patients at risk, comprehensive assessment, and the implementation of prevention programs are required to reduce falls [ 41 ]. A global incidence of 0.85–1.60 falls per patient/year in hemodialysis patients has been reported [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have concluded that focus on the identification of patients at risk, comprehensive assessment, and the implementation of prevention programs are required to reduce falls [ 41 ]. A global incidence of 0.85–1.60 falls per patient/year in hemodialysis patients has been reported [ 42 ].…”
Section: Discussionmentioning
confidence: 99%